Forest Ecosystem Multifunctionality: A Systematic Review of Measures and Drivers - Jenickson R. S. Costa; Pedro H. S. Brancalion; François-Xavier Joly; Laura H. P. Simões; Jonathan Bonfanti; Guerric le Maire; Agnès Robin; Joannès Guillemot (Current Forestry Reports, 2026)
Purpose of Review Forest ecosystem multifunctionality, the capacity of forests to simultaneously deliver multiple ecosystem functions and services, is being increasingly affected by pressures stemming from anthropogenic activities and climate change. Here, we conducted a systematic literature review to explore how forest ecosystem multifunctionality was evaluated in the literature, and to identify its main drivers. Recent Findings We found that the number of publications strongly increased in recent years, mostly focused on China and Europe. Abiotic drivers were most frequently examined, ranked in decreasing importance as soil properties, site features, and climate factors. Biodiversity-related drivers were the second most studied, encompassing species composition (i.e., species identity within the forest), species richness of trees, bacteria, and fungi, and stand structural diversity. Soil-related drivers were predominantly used to evaluate belowground multifunctionality, with less consideration given to their potential effects on aboveground multifunctionality. Conversely, the effects of tree and stand attributes have commonly been considered in both above- and belowground ecosystem multifunctionality. Forest ecosystem multifunctionality is often mediated by interactions among drivers, involving both above and below-ground components. Summary Tree species and soil organism diversity (including species richness and functional diversity), stand age and stand structural diversity, emerged as crucial drivers enhancing multifunctionality both above- and belowground. Our results suggest that preserving old-growth forests, promoting long-term restoration, and expanding species-diverse forests is an effective strategy for achieving multifunctional forests. Current understanding is limited by a pronounced geographical bias, limited comparability of studies, and overlooked multifunctionally drivers, especially related to the effects of soil fauna and management practices.